Aergia: Exploiting Packet Latency Slack in On-Chip Networks - Das, Reetuparna; Mutlu, Onur; Moscibroda, Thomas; Das, Chita (IEEE Micro. Special Issue: Micro's Top Picks from 2010 Computer Architecture Conference, 2011)
A traditional network-no-chip (NoC) employs simple arbitration strategies, such as round robin or oldest first, which treat packets equally regardless of the source application's characteristics. This is suboptimal because packets can have different effects on system performance. We define slack as a key measure for characterizing a packet's relative importance. Aergia introduces new router prioritization policies that exploit interfering packets' available slack to improve overall system performance and fairness.
Selected as a 2011 Top Pick paper by IEEE Micro